Inong Balee dan Balee Inong; Kiprah Gerakan Perempuan Aceh di Era Transisi Demokrasi - Masrizal, Masrizal; Saputra, Akmal; Liyana, Cut Irna; Nurkhalis, Nurkhalis (Prodi Sosiologi FISIP Universitas Teuku Umar, 2020)
This article aims to examine the motivations, roles, ideologies and bases of two Acehnese women's movements, namely Inong Balee and Balee Inong. Inong Balee and Balee Inong are interesting to study, considering that these two women's movements are played by grassroots communities in Aceh. This study is a literature research. The results showed that the two basic women's movements were played by grassroots communities even though in their journey these two women's movements opened themselves up to the involvement of highly educated communities. These two women's movements have a very important role in making changes to the conditions of society that are not profitable and marginalized. Ideologically, these two movements are different even though they both have the goal of improving the situation of marginalized communities, Inong Balee has an ideology of ethnic nationalism with the aim of separating himself from the Republic of Indonesia, while Balee Inong has an ideology of injustice and marginalization.